UNDERSTANDING DELAYS IN RETINOBLASTOMA DIAGNOSIS IN CHILDREN: INSIGHTS FROM A TERTIARY CARE HOSPITAL IN PAKISTAN - ASIF, M; MALIK , A; MUNEER , M; RAO , MRQ; FATIMA , M; AADIL , N (Biological and Clinical Sciences Research Journal, 2024)
Retinoblastoma, a rare but life-threatening pediatric ocular malignancy, requires early diagnosis and treatment to ensure better outcomes. However, many children, especially in developing countries like Pakistan, present late due to various socio-economic, cultural, and healthcare access barriers. Understanding these factors is critical to improving early detection and timely treatment. Objective: This study aims to identify the factors contributing to the delayed presentation of retinoblastoma in children at a tertiary care hospital in Pakistan. A cross-sectional survey utilizing a structured questionnaire. The study was conducted at the Pediatric Ophthalmology Department, Nishtar Hospital, Multan, from January 2024 to July 2024. Methods: A total of 90 mothers of children diagnosed with retinoblastoma were surveyed. Data were collected on patient demographics, initial symptoms, and time intervals between symptom onset and hospital presentation. The study examined factors such as the time to consult a general practitioner and the time lapse before reaching the tertiary care center, alongside variables like gender, age, disease laterality, socioeconomic background, and access to medical care. An oncologist performed a general physical examination, while a pediatric ophthalmologist performed a detailed eye examination under anesthesia. Statistical analysis was conducted using SPSS version 20, and Pearson’s Chi-square test was used to determine the significance of the factors associated with delays. Results: Of the 90 participants, 63% (n=57) presented with delayed diagnosis and treatment. The key contributing factors were residence in rural areas (48%, n=43), financial constraints (58%, n=52), social pressure (22%, n=20), lack of awareness about the severity of the disease (55%, n=50), limited transportation (49%, n=44), fear of enucleation (39%, n=35), and reliance on non-medical or alternative treatments (29%, n=26). Additionally, a significant number of participants (36%, n=32) reported that superstition played a role in delaying medical consultation, with many initially seeking help from religious figures for dua or dam (prayers or spiritual healing) as a means of resolving the condition. All these factors contributed statistically significantly to delays in diagnosis and treatment (p < 0.05).Conclusion: The study identifies significant barriers to timely diagnosis and treatment of retinoblastoma in children. Addressing these issues, particularly in rural areas, through improved healthcare infrastructure and public awareness could promote earlier diagnosis and better treatment outcomes for children in Pakistan.